O istotnych aspektach biegania w świetle leksyki socjolektalnej (na podstawie artykułów poświęconych treningom zamieszczonych na portalach biegowych) - Kijak, Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2015)
The aim of the article is to show the most important contemporary aspects of running on the basis of the most common sociolectal units. The analyzed material comes from articles concerning training found on websites for runners. The analysis conducted is a reconnaissance, thus the article contains only preliminary observations to serve as a contribution to further research.